2014
DOI: 10.1016/j.autneu.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine and regulation of splenic sympathetic nerve discharge

Abstract: Recent lines of inquiry indicate sedatives can influence the immune system, leading to the concept of sedative-induced immunomodulation. It has been hypothesized that sedatives may alter immune responses by modulating the sympathetic nervous system, however, little information is known regarding the effects of sedatives on regulation of splenic sympathetic nerve discharge (SND), a significant omission based on the functional role that changes in splenic SND exert on splenic cytokine gene expression. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…In a recent study we reported that intravenous Dex administration produced splenic and renal sympathoinhibition in young F344 rats (Kenney et al, 2014). Because sedatives are often used under medical conditions that include elderly patients, coupled with the consideration that advancing age alters SND responsiveness (see Kenney 2010), it was plausible to test the hypothesis that visceral sympathoinhibitory responses to intravenous Dex administration would be attenuated in aged compared with young F344 rats.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent study we reported that intravenous Dex administration produced splenic and renal sympathoinhibition in young F344 rats (Kenney et al, 2014). Because sedatives are often used under medical conditions that include elderly patients, coupled with the consideration that advancing age alters SND responsiveness (see Kenney 2010), it was plausible to test the hypothesis that visceral sympathoinhibitory responses to intravenous Dex administration would be attenuated in aged compared with young F344 rats.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesia was induced by isoflurane (3–5%; Butler Animal Science) and maintained during surgical procedures using isoflurane (1.5%–2.5%), α-chloralose (80 mg/kg, ip; Sigma), and urethane (800 mg/kg, ip; Sigma) (Kenney et al, 2014). Maintenance doses of α-chloralose (35–45 mg/kg/hr) were administered intravenously and maintenance doses of urethane (200 mg/kg every 4 hours) were administered into the intraperitoneal space.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations